О металле эпохи средней бронзы в горной зоне Северо-восточного Кавказа - Короневский, С. H.
Koronevskij, S. N.; On the Metal Dated to the Middle Bronze Epoch in the Mountainous Regions of the North-Eastern Caucasus; engl. Résumé.